IMPLEMENTASI KEBIJAKAN HAK GUNA USAHA PERKEBUNAN SAWIT DI KECAMATAN MORI ATAS KABUPATEN MOROWALI UTARA ( Studi KebijakanHak Guna Usaha PTPN XIV/PT.SPN ) - Labiro, Richard F. (Katalogis, 2016)
This research was conducted in the Mori Atas sub-district North Morowali Regency using the theory of Merilee S. Grindle through the Content Policy such as affected interests, the type of policy impact, policymaking layout, and resources used. In addition, the Policy Environment of this theory sees it from the characteristics of the institution and its ruler. This research uses descriptive qualitative research method with research interviews type which is selected intentionally adjustedÂ  to the focus of the research, the informants are the farmers, village government of Mori Atas, officials of Land Office ofÂ  Morowali, and the Government of North Morowali. Furthermore, the data were collected through observation, both primary and secondary data, and documentation. The results showed that the implementation of Palm Estate Tenure Policy PT.PN XIV / PT.SPN is not successful, it is due to neglect of the interests of the policy namely the target group of the policy by looking at the impacts of the policy both ecological and social development that a relationship public access to the environment will be lost, in terms of policy decisions explains that from the superstructure realm between legal-political, while a lack of success of this policy is nonuse of a great resource in the implementing the policy that the target group in this case are rural farmers. In policy environment, this research finds the tendency of the repressive attitude towards the implementation of the policy properly, but it is on the contrary. The policy recipients refused Estate Tenure Policy that has been implemented.